Analisis kinerja keuangan PT Pelabuhan Indonesia (Persero) Regional 4 Manado dengan menggunakan rasio keuangan dan Common Size - Samad, Faturrahman H.; Budiarso, Novi Swandari; Tangkuman, Steven J. (Yayasan Widyantara Nawasena Raharja, 2025)
This study aims to analyze the financial performance of PT Pelabuhan Indonesia (Persero) Regional IV Manado during the period 2022–2024 using financial ratio and common size analysis. The research method employed is descriptive quantitative with secondary data obtained from the company’s financial statements. The analysis includes liquidity, solvency, profitability, and activity ratios, along with common size analysis of the financial position and income statements. The results show that the current ratio decreased from 2,284% (2022) to 240.7% (2024), while the cash ratio was only recorded in 2022 at 9.07% due to centralized cash management at the head office. Solvency ratios increased, with the Debt to Asset Ratio (DAR) rising from 32% to 38.79% and the Debt-to-Equity Ratio (DER) from 47.05% to 63.38%. Profitability ratios improved, as reflected by increases in ROA, ROE, and NPM to 28.01%, 45.76%, and 8.26% in 2024, respectively. Common size analysis revealed a higher proportion of fixed assets and liabilities, alongside a decrease in equity. Overall, the financial performance demonstrates improvements in profitability and efficiency, although cash management and capital structure remain critical areas. This study provides practical insights for financial management in state-owned port enterprises at the regional level.